SUPPLY CHAIN MANAGEMENT AND QUALITY MANAGEMENT TOWARDS COFFEE WASTE BRIQUETTE INNOVATION AS AN ALTERNATIVE FUEL SOLUTION IN INDONESIA - Musyafri, Musyafri; Syah, Tantri Yanuar Rahmat (Fakultas Ekonomi Universitas Sarjanawiyata Tamansiswa, 2024)
Coffee grounds waste briquettes are charcoal blocks, lumps, or sticks that can be burned, manufactured from coffee grounds waste that has been printed in such a shape and size with a certain pressure strength and mixed with a fuel adhesive such as tapioca flour. Coffee grounds waste as biomass waste has the potential to be used as a raw material in the production of bio briquettes due to its calorific value of 5,764 kcal/kg, which is higher than that of medium-rank coal (5,141 kcal/kg). PT. Energia Kopi Kreasindo is a biofuel briquette manufacturer that processes biomass. The surplus of coffee grounds produced by the instant coffee processing industry and their underutilization in 2022 inspired the conception of this product. This study will examine how the coffee dregs briquettes market can attain its full potential by preserving its supply chain and quality management.